Promoting physical activity, healthy eating and gross motor skills development among preschoolers attending childcare centers: Process evaluation of the Healthy Start-Départ Santé intervention using the RE-AIM framework. (June 2018) - Ward, Stéphanie; Chow, Amanda Froehlich; Humbert, M. Louise; Bélanger, Mathieu; Muhajarine, Nazeem; Vatanparast, Hassan; Leis, Anne
Highlights: The RE-AIM framework was employed to conduct a process evaluation of a physical activity and healthy eating intervention in childcare centers. The intervention had a broad reach across childcare centers in two Canadian provinces. Challenges were identified in relation to implementation and sustainability. Recommendation to address resistance to change and low levels of engagement among childcare staff. Abstract: Background: The Healthy Start-Départ Santé intervention was developed to promote physical activity, gross motor skills and healthy eating among preschoolers attending childcare centers. This process evaluation aimed to report the reach, effectiveness, adoption, implementation and maintenance of the Healthy Start-Départ Santé intervention. Methods: The RE-AIM framework was used to guide this process evaluation. Data were collected across 140 childcare centers who received the Healthy Start-Départ Santé intervention in the provinces of Saskatchewan and New Brunswick, Canada. Quantitative data were collected through director questionnaires at 10 months and 2 years after the initial training and analyzed using descriptive statistics. Qualitative data were collected throughout the intervention. Results: The intervention was successful in reaching a large number of childcare centres and engaging both rural and urban communities across Saskatchewan and New Brunswick. Centres reported increasing opportunities for physical activity and healthy eating, which were generally low-cost, easy and quick to implement. However, these changes were rarely transformed into formal written policies. A total of 87% of centers reported using the physical activity resource and 68% using the nutrition resource on a weekly basis. Implementation fidelity of the initial training was high. Of those centers who received the initial training, 75% participated in the mid-point booster session training. Two year post-implementation questionnaires indicated that 47% of centers were still using the Active Play Equipment kit, while 42% were still using the physical activity resource and 37% were still using the nutrition resource. Key challenges to implementation and sustainability identified during the evaluation were consistent among all of the REAIM elements. These challenges included lack of time, lack of support from childcare staff and low parental engagement. Conclusions: Findings from this study suggest the implementation of Healthy Start-Départ Santé may be improved further by addressing resistance to change and varied levels of engagement among childcare staff. In addition, further work is needed to provide parents with opportunities to engage in HSDS with their children.